2023
DOI: 10.1136/tc-2022-057805
|View full text |Cite
|
Sign up to set email alerts
|

Vaping in a heavily regulated setting: cross-sectional survey of e-cigarette use, perceptions and social media exposure

Abstract: BackgroundSingapore has completely banned e-cigarettes and the government’s cautious stance against vaping has been consistent. Despite this, vaping appears to have gained popularity in Singapore, especially among younger people. With the heavy marketing of vaping products on social media, it is possible that such marketing, due to its cross-border nature, is reaching younger Singaporeans and driving changes in vaping-related perceptions or behaviours. This study examines their exposure to vaping-related conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The participants in this study mentioned seeing e-cigarette advertising mainly through social media platforms, such as Instagram and Facebook, similar to previous research conducted in Singapore 32 . The university students in our study reported seeing e-cigarette media via TikTok more than YouTube, which is slightly different from the adult participants from a previous study in Singapore, which may be due to the popularity of TikTok over YouTube in the younger generation in Thailand.…”
Section: Discussionsupporting
confidence: 81%
“…The participants in this study mentioned seeing e-cigarette advertising mainly through social media platforms, such as Instagram and Facebook, similar to previous research conducted in Singapore 32 . The university students in our study reported seeing e-cigarette media via TikTok more than YouTube, which is slightly different from the adult participants from a previous study in Singapore, which may be due to the popularity of TikTok over YouTube in the younger generation in Thailand.…”
Section: Discussionsupporting
confidence: 81%
“…Roberts et al's 18 study of organised opposition by Juul to prevent local flavour bans shows the challenges of implementing such parameters, while Ng et al highlight the ubiquity of exposure to e-cigarette marketing and how it can create positive perceptions of products, even in markets where they are completely banned. 19 Using waves 1 to 5 data from the Population and Health study, Krishnan et al 20 modelled trajectories of electronic nicotine delivery systems (ENDS) and cigarette use and found that prior to 2019, ENDS use did not contribute substantially to increased population-level smoking cessation. They note ongoing ENDS market changes as a factor to be considered in monitoring trajectories of dual use.…”
Section: Editorialmentioning
confidence: 99%